ANALISIS MANAJEMEN PERSEDIAAN PADA PT.UNITED EQUIPMENT INDONESIA CABANG PONTIANAK - B31111158, Muhammad Nur Arifin (Jurnal Manajemen Update, 2015)
PT. United Equipment Indonesia Pontianak branch has implemented a number of policies, but also did not rule out the possibility that inventory control is also done based on experience and intuition. With the intuition that this is done can certainly affect its not optimal procurement of spare parts. Problems often occur in a company that supplies. Inventory control policy will affect the performance of the company's performance in meeting the demand of customers and regulate supply companies. PT. United Equipment Indonesia, Pontianak Branch is one of the distributor for heavy equipment ( Heavy Equipment ) various kinds of brands, which is also tied to inventory problems. In terms of services, PT. United Equipment Indonesia Pontianak branch can already be quite optimal in serving and meeting the needs of customers, it can be seen from as much as 99% ratio of services provided by PT, United Equipment Indonesia, and inventory turnover (Inventory Turn Over) by 175 for fast moving goods , 167 for the middle 88's moving and slow-moving. Based on calculations, the safety stock for as many as 102 items of group A, group B and group C as many as 101 of 93 items. Reorder point for goods, namely when the A 204, item B when 202 C while the goods as much as 186. The method used in this research that EOQ method and its comparison is company policy PT.United Equipment Indonesia. This study concludes that companies can more efficiently and minimize the amount of fees to meet the demand if it has stock in the warehouse for each classification. Comparison of total cost for the policy used by PT. United Equipment Indonesia, Pontianak Branch as many as Rp.448.252.725 per year, whereas using EOQ method, the total cost of which was obtained by Rp.15.472.050 Keywords: ABC method. Safety Stock, Reorder Point, Economic Order Quantity, Inventory